MONITORING OF THE SOIL-CEMENT PILES BUILDINGS SETTLEMENTS - Zotsenko М. L.; Vynnykov, Yu. L.; Bondar, V. O.; Novokhatniy, V. G. (Academic journal Industrial Machine Building Civil Engineering, 2018)
In the paper it is discussesed new experimental and theoretical developments on soil-cement pile produced by drilling-mixing method. The biggest focus were made on field samples and full scale tests of the soil-cement piles, long term geodetic observations of the constructions settlements. Those experiences were implemented in Ukrainian normative documents. Geodesic monitoring of nine-ten storey building (with soil-cement piles length 6 m and diameter 500 mm in wet loess foundations) have shown that the settlements of its sections is much smaller than the ultimate values in national requirements.